Effectiveness of the graded transport mode for the intrahospital transport of critically ill patients: A retrospective study - Ling, Lijing; Xia, Xiaohua; Yuan, Hua; Liu, Shifang; Guo, Zhiqiang; Zhang, Caihong; Ma, Jin (Frontiers in Public Health, 2023)
Aim The purpose of this study was to evaluate the effectiveness of the graded transport mode in the intrahospital transport (IHT) of critically ill patients. Methods This is a retrospective study, including 800 patients and categorized them into control and observation groups. The control group included 420 critically ill patients who were transported via conventional methods from our emergency resuscitation unit from June 2017 to December 2017. The observation group included 380 critically ill patients who were transported through a graded transport mode from January 2018 to June 2018. We performed intergroup comparisons of the incidence rates and causes of adverse events (AEs), transport time, length of stay, and mortality rate. Results The observation group had significantly lower transport time and AE incidence rates than the control group. However, no significant differences were observed in terms of the length of stay and mortality rate between the two groups. Conclusion The most notable merits of the graded transport mode in the IHT of critical care patients include the fact that it significantly reduces the incidence of AEs during IHT, shortens the transport time, and improves transport efficiency, thereby ensuring the safety of critically ill patients.